Relevance Of Fukushima Nuclear Accident to India: Nuclear Radiation Risk and Interventions to Mitigate Adverse Fallout - Yadav , Kapil; Varshney, Neha; Aslesh , OP; Karmakar , MG; Pandav , Chandrakant S (National Journal of Community Medicine, 2012)
The environmental radiation release from Fukushima nuclear power following tsunami in Japan has once again highlighted the omnipotent risk of radiation injury in the today’s world. India is at a real risk from radiation fallout both due to nuclear power plant accidents and nuclear warfare threat. The risk from nuclear radiation accident in India is further increased by the region being endemic for iodine deficiency as adverse effects following nuclear radiation fallout like thyroid cancer is significantly higher in iodine deficient populations .There is need to institute disaster preparedness measures to mitigate the damage in case of a nuclear accident. Interventions to control adverse fallout of nuclear radiation include evacuation, sheltering and food controls as well as iodine prophylaxis.